PENERAPAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (E-GOVERNMENT) DENGAN PENDEKATAN BOTTOM-UP BERBASIS WEB DI SUMATERA BARAT - Yuhefizar Yuhefizar; Heri Sanjani; Rivanol Chadri (Prosiding Seminar Nasional USM, 2019)
The issuance of Presidential Regulation Number 95 of 2018 concerning Electronic-Based Government System (SPBE) and the issuance of Ministry of Administrative and Bureaucratic Reform Regulation No. 5 of 2018 concerning SPBE Evaluation Guidelines signifies the Government's seriousness in efforts to realize an integrated and comprehensive electronic-based government in Indonesia to achieve high-performance bureaucracy and public services. However, its implementation is still constrained by many factors, especially very dependent on the central agency (top-down). In this study we propose the concept of implementing SPBE with a bottom-up approach, namely through the Village / Nagari as the lowest government unit with a program called Desa-Nagari Digital. Desa-Nagari Digital is an integrated service concept using website-based information technology. From 15 Desa-Nagari in West Sumatra as a sample of the application of Desa-Nagari Digital it can be concluded that this method can be a new alternative in accelerating the application of SPBE in Indonesia.